2018
DOI: 10.3389/fmicb.2018.02299
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Emergence of Extended-Spectrum Cephalosporin-, Carbapenem- and Colistin-Resistant Gram Negative Bacteria of Animal Origin in the Mediterranean Basin

Abstract: In recent years, extended ESBL and carbapenemase producing Gram negative bacteria have become widespread in hospitals, community settings and the environment. This has been triggered by the few therapeutic options left when infections with these multi-drug resistant organisms occur. The emergence of resistance to colistin, the last therapeutic option against carbapenem-resistant bacteria, worsened the situation. Recently, animals were regarded as potent antimicrobial reservoir and a possible source of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 174 publications
5
67
1
Order By: Relevance
“…Also, eight E. coli strains isolated from street food (n = 3), surface water (n = 2) and healthy human gut (n = 3) had the macrolide resistance gene mphA, which reflects the higher percentage of erythromycin and azithromycin resistance within the isolates (Table 3). Although we have not tested the strains for plasmid carriage, ESBL and mcr-1 genes can co-exist on the same plasmid and therefore could facilitate dissemination of colistin resistance [34]. The E. coli strains carrying mcr-1 were heterogenous genetically, as confirmed by PFGE ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Also, eight E. coli strains isolated from street food (n = 3), surface water (n = 2) and healthy human gut (n = 3) had the macrolide resistance gene mphA, which reflects the higher percentage of erythromycin and azithromycin resistance within the isolates (Table 3). Although we have not tested the strains for plasmid carriage, ESBL and mcr-1 genes can co-exist on the same plasmid and therefore could facilitate dissemination of colistin resistance [34]. The E. coli strains carrying mcr-1 were heterogenous genetically, as confirmed by PFGE ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies have shown food and the environment to contain ARG found in pathogenic bacteria (12, 23, 24). Environmental reservoirs of ARG-containing pathogens include lakes and rivers (18), wastewater treatment plants (25, 26), houseflies (27), livestock (12, 28, 29), soil and manure (29, 30), retail meat products (12, 3133), companion animals (5, 6, 8, 28, 34), alfalfa sprouts (35), retail spinach (15), and other vegetables (36). The findings from these studies indicate that human health may be impacted by uptake of pathogens from the environment, many of which harbor ARG on mobile genetic elements.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are also used in food animal production as growth promoters. Extensive use of antibiotics over the last several decades has led to the rapid emergence and spread of resistant microbes, especially among enteric bacteria (11, 12). Due to the nature and complexity of the microbial communities harbored in our intestinal environment, the human gut has been recognized as a potential reservoir of ARG (3, 13, 14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the widespread use of β-Lactam antimicrobial in human and veterinary medicine, the number of extended-spectrum β-lactamase (ESBL)-producing E. coli is rising rapidly worldwide [16,17]. In addition, relevant studies on CREC have been increased in worldwide scale, while CREC is multi-drug resistant microorganism that is difficult to treat and has a high fatality rate on infection [18,19].…”
mentioning
confidence: 99%